Quantitation of intact monoclonal antibody in biological samples: comparison of different data processing strategies. (4th July 2018) - Qiu, Xi; Kang, Lijuan; Case, Martin; Weng, Naidong; Jian, Wenying
Aim: Sample extraction using immuno-affinity capture coupled with LC–high-resolution mass spectrometer has recently emerged as a novel approach for the determination of concentrations of large molecules at intact level in biological matrix.Methodology: In the current work, different data processing strategies for intact protein bioanalysis, deconvoluted mass spectra or extracted ion chromatogram, were applied to quantitate monoclonal antibody in biological samples for comparison of assay performance.Conclusion: Both deconvolution and extracted ion chromatogram strategies showed similar selectivity, sensitivity, accuracy and precision. The monkey pharmacokinetics data obtained from both approaches agreed well with each other, and agreed with data obtained from surrogate peptide approach. The pros and cons, and optimal parameters of each approach were discussed.